Best practices in rewarding and recognising employee achievements : submitted in partial fulfilment of the requirements for the degree of Masters of Philosophy, Institute of Technology and Engineering, College of Sciences, Massey University - Campbell-Allen, Nicola (Massey University, 2008)
Managers and Human Resource professionals are constantly seeking answers to the issue of how best to reward and recognise (R & R) their employees. Whilst there is a raft of international information the need for New Zealand-based research has been identified. The focus of this study is on Reward and Recognition (R & R) practices in New Zealand organisations so that key findings, best practices and/or recommendations in this important area can be identified and shared with other New Zealand organisations. This study involved a three phase methodology (1) a review of international and national literature on R & R, (2) the collection and analysis of quantitative data using an electronic e-mail survey, and (3) the collection and analysis of qualitative data using a structured interview process with eight organisations considered to be best practice. This thesis provides discussion on: • The impetus for this study; • Key themes from the literature; • The development of a model for rewarding and recognising employees; • Quantitative results from the survey. • Qualitative findings from the interview process; and • Key findings for organisations wishing to implement a R & R strategy.
Keywords: New Zealand; Employee motivation; Incentives in industry